Kepemimpinan Pembelajaran Kepala Sekolah dalam Penguatan Profesionalisme Guru Berbasis Pesantren di TK PAS Nurul Qur’an Bungkal Ponorogo - Uyuni, Tiyana Nur; Sulton, Sulton (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
Principal Instructional Leadership in Strengthening Pesantren-Based Teacher Professionalism at TK PAS Nurul Qur’an Bungkal Ponorogo". Early childhood education (ECE) plays a strategic role in building children’s cognitive, socio emotional, moral, and spiritual foundations. Teacher professionalism is a crucial factor in ensuring the quality of learning, particularly in pesantren-based kindergartens where academic instruction is integrated with Islamic values. Teacher professionalism is strongly influenced by school leadership, especially instructional leadership. This study aims to describe the instructional leadership of the principal in strengthening teacher professionalism in a pesantren-based kindergarten at TK PAS Nurul Qur’an Bungkal Ponorogo. This research employed a qualitative descriptive approach involving the principal and kindergarten teachers selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using descriptive qualitative techniques through data categorization, interpretation, and thematic conclusion drawing. The findings indicate that the principal implemented instructional leadership by prioritizing learning quality as the core focus of school management. Instructional leadership was manifested through active involvement in lesson planning, collaborative academic supervision, and continuous teacher mentoring. These practices contributed to improved pedagogical competence, professional commitment, reflective teaching practices, and the integration of Islamic values into early childhood learning. Despite challenges such as limited facilities and administrative workload, adaptive and collaborative leadership practices were able to minimize these constraints. This study concludes that contextual, collaborative, and value-based instructional leadership plays a key role in strengthening teacher professionalism in pesantren-based kindergartens.